Wearable wireless point-of-need platform for smartphone-based analysis of electrochemical biosensors to healthcare and environmental monitoring (2022)
The work presented in this thesis has been organized into separate articles that have been published or are under review. In the first article (Chapter 2), an antibody-based biomicrosystem was developed for the bioelectrochemical detection of Mycobacterium tuberculosis ESAT-6. Results showed that, compared to the negative controls, a maximum variation of 171% between each replica was achieved when compared to samples containing ESAT-6 M. tuberculosis immunodominant protein. From this research derives a software for analyzing and differentiating the manufacturing stages of the sensor and the first version of the integrated measurement system. Three research works carried out by our group for detection of human papilloma virus (HPV), tuberculosis and Chagas are summarized like point-of-care devices technologies (Chapter 3). This time, different immobilization techniques and comparative tables in terms of ease of use, time of testing and cost, are presented. In the third article (Chapter 4) the development of a wearable full-integrated platform for an in-situ electroanalysis of laccase-based biosensors via smartphone is documented. The obtained results are tightly comparable to benchtop commercial potentiostats, with the ability to run direct tests of patient-side. A proof of concept is carried out in the last chapter (Chapter 5) through fully printed wearable microfluidic nanosensor for sweat rate, conductivity, and copper detection with healthcare applications was manufactured. The results indicate a limit of detection of 396 ppb, a linear range up to 2500 ppb and a sensitivity of 2.3 nA/ppb. Validation tests were carried out with both the developed portable system and benchtop equipment. The article includes a support document with the following information: - Comparative information between the developed platform and other platforms reported by the literature. - Design and development of the distinct parts that make up the full-integrated system. - Electrical measurements. - User's Guide.